Sulfur deposition changes under sulfate geoengineering conditions: quasi-biennial oscillation effects on the transport and lifetime of stratospheric aerosols - D. Visioni; G. Pitari; P. Tuccella; G. Curci (Atmospheric Chemistry and Physics, 2018)
Sustained injection of sulfur dioxide (SO 2 ) in the tropical lower stratosphere has been proposed as a climate engineering technique for the coming decades. Among several possible environmental side effects, the increase in sulfur deposition deserves additional investigation. In this study we present results from a composition–climate coupled model (University of L'Aquila Composition-Chemistry Model, ULAQ-CCM) and a chemistry-transport model (Goddard Earth Observing System Chemistry-Transport Model, GEOS-Chem), assuming a sustained lower-stratospheric equatorial injection of 8 Tg SO 2 yr −1 . Total S deposition is found to globally increase by 5.2 % when sulfate geoengineering is deployed, with a clear interhemispheric asymmetry (+3.8 and +10.3 % in the Northern Hemisphere (NH) and the Southern Hemisphere (SH), due to +2.2 and +1.8 Tg S yr −1 , respectively). The two models show good consistency, both globally and on a regional scale under background and geoengineering conditions, except for S-deposition changes over Africa and the Arctic. The consistency exists with regard to time-averaged values but also with regard to monthly and interannual deposition changes. The latter is driven essentially by the variability in stratospheric large-scale transport associated with the quasi-biennial oscillation (QBO). Using an externally nudged QBO, it is shown how a zonal wind E shear favors aerosol confinement in the tropical pipe and a significant increase in their effective radius (+13 % with respect to W shear conditions). The net result is an increase in the downward cross-tropopause S flux over the tropics with dominant E shear conditions with respect to W shear periods (+0.61 Tg S yr −1 , +42 %, mostly due to enhanced aerosol gravitational settling) and a decrease over the extratropics (−0.86 Tg S yr −1 , −35 %, mostly due to decreased large-scale stratosphere–troposphere exchange of geoengineering sulfate). This translates into S-deposition changes that are significantly different under opposite QBO wind shears, ...